BOUNDEDNESS OF MIKHLIN OPERATOR IN MORREY SPACE - MAHARANI (NIM: 20116014), DIAN
A multiplier operator is an operator which maps a function to the product of that function with a certain function. A Fourier multiplier operator is a multiplier operator which uses Fourier transformation of a function. S.G. Mikhlin proved the boundedness of the operator in classical Lebesgue space if the multiplier function (generator of the Fourier multiplier operator) is a bounded function. In this thesis, we prove that Fourier multiplier operator is also bounded on classical Morrey space under the same condition.